La zonificación para el desarrollo turístico del cantón Bolívar post terremoto 2016. - García García, María Leandra (2018)
The thesis general objective was to elaborate the tourist zonification of the canton Bolivar, province of Manabí post-earthquake 2016, to contribute with the development of the local tourism. The research was bibliographic, descriptive and field. For the research development of the thesis, a methodological procedure was structured according to the specific objectives: diagnosis of the current situation, evaluation of post-earthquake tourist potential and the tourist zoning of the Bolivar canton. As a result of the application of the methodological procedure, the areas most affected by the earthquake of April 16, 2016 were identified, as well as the natural and cultural tourism resources that were preserved after the earthquake. The cantonal tourism potential was evaluated through the application of a strategic SWOT matrix contributing to the determination of the strategies of the reactivation and re-empowerment of the tourist resources of the canton. Likewise, a zoning was identified identifying three environmental units: the western zone or valley, intermediate zone and eastern zone along the cantonal geography. These units gave way to the identification and zoning of three areas of sustainable tourism development and conservation: nuclear tourist zone, zone of agroturístico use and conservation; And the area of sustainable use and wildlife. Finally, the research showed that these areas have resources and facilities with potential that contribute to tourism development, concluding that tourism zoning will, in the future, cement the bases for an efficient planning and territorial planning of the Bolivar canton.